2020
DOI: 10.1093/jxb/eraa084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of root architectural plasticity in maize

Abstract: Root phenotypes regulate soil resource acquisition; however, their genetic control and phenotypic plasticity are poorly understood. We hypothesized that the responses of root architectural phenes to water deficit (stress plasticity) and different environments (environmental plasticity) are under genetic control and that these loci are distinct. Root architectural phenes were phenotyped in the field using a large maize association panel with and without water deficit stress for three seasons in Arizona and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 124 publications
0
43
0
Order By: Relevance
“…Root branching is a necessary developmental process for increasing the number of growing tips and defining the distribution of their meristem sizes (Pagès, 2014), with a large metabolic cost. Root branching was critical for plant survival and performance under abiotic conditions (Schneider et al , 2020). Two genes (Traes_1AL_9CC946A58 and Traes_1DL_7EF27C52F) underlying the largest −log 10 P signal of BF were annotated as being involved in steroid biosynthesis, which may play a role in interacting with auxin signaling to promote lateral root growth (Vriet et al , 2012; Wang et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Root branching is a necessary developmental process for increasing the number of growing tips and defining the distribution of their meristem sizes (Pagès, 2014), with a large metabolic cost. Root branching was critical for plant survival and performance under abiotic conditions (Schneider et al , 2020). Two genes (Traes_1AL_9CC946A58 and Traes_1DL_7EF27C52F) underlying the largest −log 10 P signal of BF were annotated as being involved in steroid biosynthesis, which may play a role in interacting with auxin signaling to promote lateral root growth (Vriet et al , 2012; Wang et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic plasticity of a genotype against rapid climatic fluctuations and severe drought stress requires an integrated response by different drought stress-adaptive mechanisms, such as dehydration resistance and dehydration escape or avoidance ( Levit, 1972 ; Kadam et al , 2017 ). Recently, several studies have shown that plasticity of root traits is mostly advantageous for the effective adaptation to drought stress ( Kadam et al , 2015 ; Sandhu et al , 2016 ; Schneider et al , 2020a , b ). For instance, under drought stress conditions, the plasticity of different root traits, such as root length density and total root length ( Kano et al , 2011 ; Kano-Nakata et al , 2011 , 2013 ; Tran et al , 2015 ), contributed to a greater shoot biomass and increased water use and photosynthetic efficiency levels ( Fig.…”
Section: How Do Root System Traits Mediate Tolerance To Drought Stresmentioning
confidence: 99%
“…The plasticity of root system responses also induces tolerance to drought stress by increasing the number of fibrous roots, and minimizing the lateral root diameters and root biomass fluctuations ( Osmont et al , 2007 ; Meister et al , 2014 ; Salazar-Henao et al , 2016 ). Recently, the genomic loci regulating root phenotypic plasticity under drought stress conditions in cereal crop species ( Sandhu et al , 2016 ; Kadam et al , 2017 ; Schneider et al , 2020a , b ) revealed that the plasticity of root systems might be an excellent source of genetic variation for stress adaptation ( Schneider and Lynch, 2020 ).…”
Section: How Do Root System Traits Mediate Tolerance To Drought Stresmentioning
confidence: 99%
See 1 more Smart Citation
“…These structurally and functionally diverse root types contribute to the complexity of root morphological traits in maize. Root system architecture made up of structural features, such as root length, number, diameter, total area and volume, and length of lateral roots, exhibits great plasticity in response to environmental changes and could be critical to the growth and development of maize [ 5 , 6 ]. Root system development is mediated by various plant endogenous hormones [ 7 ], among which auxin and cytokinin play key roles in root development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%